PEDAGOGICAL VIEWS ON MORAL AND CHRISTIAN EDUCATION PERSONALITIES IN LITERARY MONUMENTS XVI - FIRST HALF OF XVIII CENTURY - Hamali О.І.; Kanevska О.Б. (Pedagogy of Higher and Secondary Education, 2011)
The article deals with the principles of Christian moral education reflected in literary works of the XVI - the first half of the XVIII centuries both in Ukraine & Russia.